Assessment of PLGA-PEG-PLGA Copolymer Hydrogel for Sustained Drug Delivery in the Ear - Feng, Liang; A. Ward, Jonette; Kevin Li, S.; Tolia, Gaurav; Hao, Jinsong; I. Choo, Daniel (Current Drug Delivery, 2014)
Temperature sensitive copolymer systems were previously studied using modified diffusion cells in vitro for intratympanic injection, and the PLGA-PEG-PLGA copolymer systems were found to provide sustained drug delivery for several days. The objectives of the present study were to assess the safety of PLGA-PEG-PLGA copolymers in intratympanic injection in guinea pigs in vivo and to determine the effects of additives glycerol and poloxamer in PLGA-PEGPLGA upon drug release in the diffusion cells in vitro for sustained inner ear drug delivery. In the experiments, the safety of PLGA-PEG-PLGA copolymers to inner ear was evaluated using auditory brainstem response (ABR). The effects of the additives upon drug release from PLGA-PEG-PLGA hydrogel were investigated in the modified Franz diffusion cells in vitro with cidofovir as the model drug. The phase transition temperatures of the PLGA-PEG-PLGA copolymers in the presence of the additives were also determined. In the ABR safety study, the PLGA-PEG-PLGA copolymer alone did not affect hearing when delivered at 0.05-mL dose but caused hearing loss after 0.1-mL injection. In the drug release study, the incorporation of the bioadhesive additive, poloxamer, in the PLGA-PEG-PLGA formulations was found to decrease the rate of drug release whereas the increase in the concentration of the humectant additive, glycerol, provided the opposite effect. In summary, the PLGA-PEG-PLGA copolymer did not show toxicity to the inner ear at the 0.05-mL dose and could provide sustained release that could be controlled by using the additives for inner ear applications.
Keywords: Cidofovir